The impact of heat therapy on neuromuscular function and muscle atrophy in diabetic rats - AlSabagh, Abdullah T.; Rao, Muddanna S.; Renno, Waleed M. (Frontiers in Physiology, 2023)
Diabetes Mellitus (DM) is the most common metabolic disease worldwide and is associated with many systemic diabetic complications. Muscle atrophy is one of the significant complications in DM patients, making routine tasks laborious as atrophy continues. It is known that heat stress stimulates heat shock proteins and other proteins that maintain muscle mass; however, it is not thoroughly studied in diabetic conditions. This study addressed whether heat therapy can attenuate muscle atrophy in STZ-induced diabetic rats and explored its mechanism of action on specific muscle proteins. Male Sprague Dawley rats were randomly divided into short-term (3 weeks) and long-term (6 weeks) experiments. In each experiment rats were divided into control, heat therapy, diabetic and diabetic+heat therapy groups. Rats in heat therapy groups were exposed to heat therapy for 30 minutes daily for three or six weeks in a temperature-controlled (42oC) chamber. The attenuation of neuromuscular functions assessed by Rotarod, Kondziella's inverted screen, and extensor postural thrust tests showed that diabetic rats exposed to heat therapy performed significantly better than diabetic controls. Muscle cross sectional area data established that heat therapy reduced muscle atrophy by 34.3% within three weeks and 44.1% within six weeks in the diabetic groups. Further, heat therapy significantly decreased muscle atrophy markers (CD68, KLF, and MAFbx) and significantly elevated muscle hypertrophy markers (AKT, mTOR, and HSP70). This study shows the relevance and clinical significance of utilizing heat therapy as a viable treatment to attenuate muscle atrophy in diabetic patients.